Effect of fly ash content towards Sulphate resistance of oil palm shell lightweight aggregate concrete - Khairunisa, Muthusamy; Fadzil, Mat Yahaya; Muhammad Nazrin Akmal, Ahmad Zawawi; Saffuan, Wan Ahmad; Nur Azzimah, Zamri; Mohd Hanafi, Hashim; Mohd Hafizuddin, Rasid (IOP Publishing Ltd, 2018)
Both oil palm shell (OPS) and fly ash are by-product generated from the industries. Disposal of these by-product as wastes cause negative impact to the environment. The use of both oil palm shell and fly ash in concrete is seen as an economical solution for making green and denser concrete. The primary aim of this research is to determine the effects of FA utilization as sand replacement in oil palm shell lightweight aggregate concrete (OPS LWAC) towards sulphate resistance. Five concrete mixes containing fly ash as sand replacement namely 0%, 10%, 20%, 30% and 40% were prepared in these experimental work. All mixes were cast in form of cubes before subjected to sulphate solution for the period of 5 months. It was found that addition of 10% fly ash as sand replacement content resulted in better sulphate resistance of OPS LWAC. The occurrence of pozzolanic reaction due to the presence of FA in concrete has consumed the vulnerable Calcium hydroxide to be secondary C-S-H gel making the concrete denser and more durable.